Strategi Pemasaran Dalam Meningkatkan Jumlah Nasabah Produk Pembiayaan Pensiun PT. BSI KCP Lubuk Basung - Delya Putri, Fani; Kenedi, Jon (Risalah Iqtishadiyah, 2024)
The growth of pension financing product customers at PT. BSI KCP Lubuk Basung from 2021-2023 has increased, but the difference in the number of customers per year is relatively small and the total contract value per year has not reached the target. Therefore, the study aims to develop a strategy to be implemented by PT. BSI KCP Lubuk Basung in increasing the number of pension financing product customers. In an increasingly competitive context, where various financial institutions offer similar products and are located in adjacent areas, the right approach is needed to win market competition. This study uses a quantitative descriptive method with a field approach to observe the phenomena that occur at the research location. Data collection was carried out through observation, interviews, and documentation. The data analysis techniques applied include SWOT analysis, IFE and EFE matrix analysis, and SWOT matrix analysis and score weighting. Based on the analysis carried out, certain strategies can be implemented by PT. BSI KCP Lubuk Basung to significantly increase the number of pension financing product customers by using the SO strategy, namely developing pension financing products by utilizing available technology and relying on skilled human resources. Increase promotion through various media and direct socialization (door-to-door). Improve the quality of service to customers with professional service. Strengthen the brand while maintaining its sharia values ​​as the main identity.